(untitled) (Al-Academy, 2025)
Education is considered a tool and means of development, as it enables achieving efficiency in performance and production if it is properly invested and employed. It also has a return and a return that appears in building the productive and effective human element, which in turn contributes to increasing production efficiency. The Blackboard system software allows the teacher to upload the materials he is teaching to a website, and gives the learner the opportunity to continue the learning process, as it opens the way for learners to communicate and interact with each other, and communicate with their teachers in order to do joint work in new and enjoyable ways, and helps educational institutions in Transforming the Internet into a powerful medium in the education process. Sewing techniques vary according to the nature of the clothing product, and incomplete sewing is one of the major defects that reduce the value of the clothing product. Sewing is one of the most important processes in the manufacture of ready-made clothing because it is the basic pillar that preserves the shape, design and performance of the garment. The research aims to : 1- Building an educational unit with the “Blackboard” system to train female students on clothing manufacturing techniques. 2- Applying the educational unit on the “Blackboard” system to train female students on clothing manufacturing techniques. 3- Measuring the effectiveness of applying the educational unit using the “Blackboard” system in providing female students with special knowledge of clothing manufacturing techniques. 4- Measuring the effectiveness of applying the educational unit using the “Blackboard” system in developing female students’ skills to implement clothing manufacturing techniques. The search found : 1- There are statistically significant differences between the average scores of female students in the pre- and post-application of the educational unit on the “Blackboard” system for training on clothing manufacturing techniques, in favor of the post-application. 2- There are statistically significant differences between the average scores of female students in the pre- and post-application of the achievement test in favor of the post-application. 3- There are statistically significant differences between the average scores of female students in the pre- and post-application of the skill performance test in favor of the post-application. The research recommended : 1- Establishing electronic educational units to raise the level of female students’ knowledge and skills in the field of clothing manufacturing and production to keep pace with developments in the local market for the clothing industry. 2- Encouraging female faculty members to develop academic curricula using modern educational methods and strategies to raise the academic level of female students. 3- Applying the results of the current research to specialized and non-specialized female graduates to develop their knowledge and skills regarding the ready-made garment industry, which will enable them to establish small projects.